The burden and temporal trend of early onset pancreatic cancer based on the GBD 2021 - Zongbiao Tan; Yang Meng; Yanrui Wu; Junhai Zhen; Haodong He; Yu Pu; Jixiang Zhang; Weiguo Dong (npj Precision Oncology)
Abstract In the context of the global increase in early-onset tumours, investigating the global disease burden caused by early-onset pancreatic cancer (EOPC) is imperative. Data on the burden of EOPC were obtained from the Global Burden of Disease Study 2021. A joinpoint regression model was used to analyse the temporal trend of the EOPC burden, and an age‒period‒cohort (APC) model was used to analyse the influence of age, period, and birth cohort on burden trends. Globally, the number of EOPC cases increased from 24,480 to 42,254, and the number of deaths increased from 17,193 to 26,996 between 1990 and 2021. The results of the APC model showed that the burden of EOPC increases with increasing age, whereas the variations in period and cohort effects exhibited a complex pattern across different sociodemographic index regions. Consequently, the disease burden of EOPC is increasing worldwide, highlighting the need for effective interventions.